2005
DOI: 10.1016/j.nuclphysa.2004.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Band structure effects for dripped neutrons in neutron star crust

Abstract: Abstract. The outer layers of a neutron star are supposed to be formed of a solid Coulomb lattice of neutron rich nuclei. At densities above neutron drip density (about one thousandth of nuclear saturation density), this lattice is immersed in a neutron fluid. Bragg scattering of those dripped neutrons by the nuclei which has been usually neglected is investigated, within a simple mean field model with Bloch type boundary conditions. The main purpose of this work is to provide some estimates for the entrainmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
183
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(192 citation statements)
references
References 35 publications
(62 reference statements)
8
183
1
Order By: Relevance
“…This prediction has now been confirmed by an analysis [7] based on the phenomenological model of Oyamatsu et al [26] where values as large as m ⋆ /m ∼ 15 has been found at a baryon density n b = 0.03 fm −3 . Our present analysis indicates that this conclusion will not be significantly affected by taking the relevant pairing gap ∆ into account.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…This prediction has now been confirmed by an analysis [7] based on the phenomenological model of Oyamatsu et al [26] where values as large as m ⋆ /m ∼ 15 has been found at a baryon density n b = 0.03 fm −3 . Our present analysis indicates that this conclusion will not be significantly affected by taking the relevant pairing gap ∆ into account.…”
Section: Discussionmentioning
confidence: 55%
“…Recent numerical work [7] has shown that this treatment implies an enormous enhancement by the entrainment of the effective mass of the free neutrons in the middle layers of the inner crust (a result that contrasts with the rather moderate diminution predicted for the effective neutron mass in the deeper core layers). The purpose of the present work is to evaluate the adjustments -which turn out to be small -that will result from allowance for the superfluid pairing of the neutrons.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations